1999
DOI: 10.1002/1522-7189(200009/10)7:5<175::aid-nt63>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Fungal degradation of aflatoxin B1

Abstract: A number of fungal cultures were screened to select an organism suitable to be used in the detoxification of aflatoxin B1. They were co-cultured in Czapek-Dox-Casamino acid medium with aflatoxin B1 producing Aspergillus flavus. Several fungal cultures were found to prevent synthesis of aflatoxin B1 in liquid culture medium. Among these Phoma sp., Mucor sp., Trichoderma harzianum, Trichoderma sp. 639, Rhizopus sp. 663, Rhizopus sp. 710, Rhizopus sp. 668, Alternaria sp. and some strains belonging to the Sporotri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 5 publications
0
42
0
3
Order By: Relevance
“…SF, and Alternaria sp. have been shown to degrade AFB 1 to levels between 65% and 99% in 5 days at 28 ± 2 • C. 119 Similarly, Varga et al 231 reported the ability of various Aspergillus strains such as A. fumigatus, A. japonicus, and A. niger to degrade OTA in liquid YES media, with A. niger degrading OTA to ochratoxin-α and phenylalanine in solid media and liquid cultures. Additionally, Acinetobacter calcoaceticus has been shown to degrade 100% of OTA in ethanol minimal salts medium at an initial OTA concentration of 10 µg ml −1 at 30 • C within 120 h. 232 Various fermentation processes have also been shown to result in reducing the toxic effects of mycotoxins.…”
Section: Biological Methodsmentioning
confidence: 99%
“…SF, and Alternaria sp. have been shown to degrade AFB 1 to levels between 65% and 99% in 5 days at 28 ± 2 • C. 119 Similarly, Varga et al 231 reported the ability of various Aspergillus strains such as A. fumigatus, A. japonicus, and A. niger to degrade OTA in liquid YES media, with A. niger degrading OTA to ochratoxin-α and phenylalanine in solid media and liquid cultures. Additionally, Acinetobacter calcoaceticus has been shown to degrade 100% of OTA in ethanol minimal salts medium at an initial OTA concentration of 10 µg ml −1 at 30 • C within 120 h. 232 Various fermentation processes have also been shown to result in reducing the toxic effects of mycotoxins.…”
Section: Biological Methodsmentioning
confidence: 99%
“…(Cole & Kirksey, 1971), Corynebacterium rubrum (Mann & Rehm, 1976), Phoma sp. (Shantha, 1999), Rhodococcus erythropolis and Mycobacterium fluoranthenivorans sp. nov (Teniola et al, 2005) and nontoxigenic strains of A. flavus and A. parasiticus (Dorner et al, 2003) and physical detoxification of aflatoxins by hydrated sodium calcium aluminosilicate (Harvey et al, 1989;Phillips, Kubena, Harvey, Taylor, & Heidelbaugh, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…and Aspergillus fl avus followed by A. chevalieri Thom & Church, A. fumigatus, Penicillium spp. Other factors affecting mycotoxin concentration include microbial genetics, minimum climatic conditions (moisture content, temperature), substrate, variations within species, the presence of other fungal species, 25 and the geographic distribution of mycotoxin -producing fungi. Link, and Basipetospora species.…”
Section: Foodmentioning
confidence: 99%